2020
DOI: 10.18231/j.jchm.2020.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of tension headache among medical students during their clinical years at King Abdulaziz University in Jeddah, 2019

Abstract: Background: Tension-type headache (TTH) is the most common primary headache disorder among medical students. It affects academic performance and the quality of the student's daily lives.Objective: This study aimed to investigate the prevalence of TTH and associated factors among students at King Abdulaziz University (KAU) in Jeddah, Saudi Arabia. Methods: A cross-sectional study involved students at KAU in the academic years from 4th to 6th grades during the calendar year of 2019. For sampling purposes, we ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
1
1
Order By: Relevance
“…The prevalence of TTH was found to be 40.3% in the current study within the global prevalence rate of 12%–78% 22 . Studies from Syria, 23 Turkey, 24 and Nigeria 25 reported much lower prevalence while another study from Saudi Arabia showed a similar prevalence 26 . For TTH, no significant difference was with age, sex, year of study, and staying with the hostel, which is supported by findings of Alkarrash et al., 23 Syria.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of TTH was found to be 40.3% in the current study within the global prevalence rate of 12%–78% 22 . Studies from Syria, 23 Turkey, 24 and Nigeria 25 reported much lower prevalence while another study from Saudi Arabia showed a similar prevalence 26 . For TTH, no significant difference was with age, sex, year of study, and staying with the hostel, which is supported by findings of Alkarrash et al., 23 Syria.…”
Section: Discussionsupporting
confidence: 83%
“…The result is similar but higher than the result from a survey done by Ekenze et al 19 According to a study done by Nabeel et al, headaches can be caused by numerous factors, such as academic stressors, psychosocial stressors, decreased quality and quantity of sleep, and reduced caffeine intake. 20 The different result between this study and the study by Ekenze et al is caused by some differences in the research procedure. Ekenze et al used the diagnosis from a neurologist, so it was more accurate than the results from questionnaires.…”
Section: Discussioncontrasting
confidence: 74%
“…The difference was caused by the amount of inclusion and exclusion criteria in Nabeel et al's study, which was lower than the number of measures in this study. 20 The participants in this study who suffered Like stress, the prevalence of tension-type headaches in this study is also higher in The difference in muscle structure between men and women and the higher amount of active trigger points in women causes this. 22 Another study conducted by Abboud et al also said that women have a lower pain threshold, which makes women more sensitive to pain than men.…”
Section: Discussionmentioning
confidence: 62%
“…Its severity is directly proportional to its negative impact, which includes decreased academic performance, absenteeism, and discipline failures, as well as decreased quality of life and an increase in the identification of comorbid psychiatric problems. 3 A few studies have also discovered a link between medical students' QoL and an increased risk of depression, burnout, and suicidal thoughts. Health-related quality of life (HR-QoL) is a multifaceted notion that encompasses respondents' subjective perceptions of their physical and mental well-being.…”
Section: Introductionmentioning
confidence: 99%